Life-Giving Breath Life-Giving Breath: Ecological Pneumatology in the Context of Fetishization. - Bergmann, Sigurd (Ecumenical Review, 2013)
In this article, the author discusses the need today to revise Christian pneumatology. The author mentions that the Spirit's divinity and agency in the history of salvation are clearly manifested in such Biblical passages as John 1:32. The author relates that after the first ecumenical age, the role of pneumatology in the history of Christian doctrine has been reduced. The article also explains the origin of pneumatology as well as the reason for the Spirit's indwelling of human beings.